From Leadership to Innovation: Understanding the Motivation to Learn - Chidir, Gusli; Kumoro, Dwi Ferdiyatmoko Cahya; Mariyanah, Siti; Nadeak, Multi; Bonar Bangun Jeppri, Bonar Bangun Jeppri (IJOSMAS, 2022)
- The purpose of this study was to apply the influence of transformational leadership on employees' innovative work behavior, and the mediating role of learning motivation on the relationship between transformational leadership and innovative work behavior. The questionnaire, designed as a self-reported survey, was distributed to permanent employees of a manufacturing company in the automotive sector. Data was collected from 203 employees. The hypothesis was tested using structural equation modeling. Data processing using SEM method with SmartPLS 3.0 software. The findings show that transformational leadership has a positive impact on employee innovative work behavior and motivation to learn to mediate the relationship between transformational leadership and innovative work behavior. This study contributes to the existing literature by providing empirical evidence on the effect of transformational leadership on employees' innovative work behavior as well as the impact of innovative work behavior variables. The implication is that organizations should pay attention to creating a climate that supports innovation and encourages individuals to learn new knowledge and skills, and provides employees with opportunities to use their acquired knowledge and skills